Multidimensional analysis of public open spaces: urban morphology, parametric modelling and data mining - Lopes, João V. (2015)
Public open spaces (parks, squares and other gathering places) can only be grasped from a simultaneous view of their attributes. In an ongoing Phd research project we propose to overcome the limitations of traditional-descriptive urban morphology methods in dealing with this simultaneity derived from their many shapes, functions, uses and relations within the urban structure. After developing the relations between formal attributes and intangible spatial properties, their identity and proximity may be disclosed by multivariate statistical analysis and data mining techniques. We outline a multidimensional method for the synchronic analysis and classification of the public open spaces departing from a research corpus of 126 Portuguese urban squares, whose analysis is intended to interactively (re)define it. The work done so far is presented, which comprises: (i) firming the concepts, criteria and attributes to extract; (ii) survey on theories, methods and spatial analysis tools and shortcomings identification; (iii) adaptation and/or creation of new methods and tools; (iv) creation of databases from CAD and GIS environments; (v) research on multivariate analysis, data mining and data visualization techniques.